Error-prone signalling. - Johnstone, R; Grafen, A (1992)
The handicap principle of Zahavi is potentially of great importance to the study of biological communication. Existing models of the handicap principle, however, make the unrealistic assumption that communication is error free. It seems possible, therefore, that Zahavi's arguments do not apply to real signalling systems, in which some degree of error is inevitable. Here, we present a general evolutionarily stable strategy (ESS) model of the handicap principle which incorporates perceptual error. We show that, for a wide range of error functions, error-prone signalling systems must be honest at equilibrium. Perceptual error is thus unlikely to threaten the validity of the handicap principle. Our model represents a step towards greater realism, and also opens up new possibilities for biological signalling theory. Concurrent displays, direct perception of quality, and the evolution of 'amplifiers' and 'attenuators' are all probable features of real signalling systems, yet handicap models based on the assumption of error-free communication cannot accommodate these possibilities.